1998
DOI: 10.1007/978-1-4471-3609-5
|View full text |Cite
|
Sign up to set email alerts
|

Laser Material Processing

Abstract: Library ofCongress Cataloging-in-Publication Data Steen, W.M.Laser material processing / William M. Steen. --2nd ed.p. COL Includes bibliographical references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(70 citation statements)
references
References 476 publications
0
65
0
5
Order By: Relevance
“…Considering the center of the groove (y = 0), the angle of inclination was zero (φ = 0). According to [1], the angle of the cutting front to the vertical axis is about 14 • . By integrating Eq.…”
Section: Formulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the center of the groove (y = 0), the angle of inclination was zero (φ = 0). According to [1], the angle of the cutting front to the vertical axis is about 14 • . By integrating Eq.…”
Section: Formulationsmentioning
confidence: 99%
“…Laser machining is one of the most popular applications of laser material processing [1]. Techniques such as laser grooving have been developed for the new demands in the machining markets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, incomplete removal and badly roughened surface were found after the process. Tarpey et al used 10.57 and 10.63 µm continuous CO 2 to strip the polyimide fiber but also failed. They found that many fibers were not properly stripped instead of charred, and some of fibers were even seen with occasional "pinholes" in the glass [9].…”
Section: Introductionmentioning
confidence: 95%
“…These lasers have short wavelengths of 1.06 mm, which may outperform CO 2 lasers for metallic materials that absorb much better at short wavelength. Nd: YAG lasers are favourable for sintering carbide ceramics owing to lower reflectivity and higher surface adsorption [7,8]. The feasibility study of SLS by Vaucher et al [9] investigated the Nd:YAG laser sintering of metal and ceramic composites including aluminium alloy/silicon carbide, titanium/silicon carbide, and titanium/graphite and single layers and multilayers of metal/ceramic composites were successfully produced.…”
Section: Introductionmentioning
confidence: 99%